Nitrogen Nutrition of Some Local Rice Varieties Grown without Fertilizer on Acid Sulphate Soil Area in South Kalimantan - Erry Purnomo; Toshihiro Hasegawa; Yasuyuki Hashidoko; Presto J Saputra; Mitsuru Osaki (UNIVERSITY OF LAMPUNG, 2009)
Banjarese farmers in South Kalimantan apply a very minimum nitrogen (N) fertilizer in growing local rice. This practice has been adopted for many years. Yet, the grain yield level at farmers’ field is not necessary low. We are questioning about N sources for the crop. This study only focuses on measuring net N mineralization in association with N uptake. We grew three rice varieties at four sites in rice growing area of South Kalimantan. The net N accumulation in soil and water, plant top biomass, N concentration of plant tissue and N uptake were measured on monthly basis. The results showed that all rice varieties grown in the 4 locations took up more N than from N mineralized from the organic matter. The higher N in the crop indicates that there are other sources of N for the local rice such as N fixed by microorganisms.